Nonaspirin Nonsteroidal Antiinflammatory Drug Use in the Nordic Countries from a Cardiovascular Risk Perspective, 2000–2016: A Drug Utilization Study. Issue 2 (8th February 2019) - Kristensen, Kasper Bruun; Karlstad, Øystein; Martikainen, Jaana E.; Pottegård, Anton; Wastesson, Jonas W.; Zoega, Helga; Schmidt, Morten
Abstract : Study Objective: Evidence on the cardiotoxicity of nonaspirin nonsteroidal antiinflammatory drugs (NSAIDs), particularly diclofenac and the newer selective cyclooxygenase (COX)‐2 inhibitors, has accumulated over the last decade. Our objective was to examine whether the use of NSAIDs in the Nordic countries changed with the emerging evidence, regulatory statements, and clinical guidelines advocating caution for the use of specific NSAIDs. Design: Drug utilization study. Data Sources: Nationwide wholesale statistics and prescription registries in Denmark, Finland, Iceland, Norway, and Sweden (2000–2016). Measurements and Main Results: Our main outcome measures were yearly total sales, expressed as number of sold defined daily doses (DDDs)/1000 inhabitants/day, and yearly prevalence of prescription use, expressed as number of prescription users per 1000 inhabitants. The DDD is the assumed average maintenance dose per day for a drug used for its main indication in adults. Total sales of NSAIDs increased in all countries and were highest in Iceland, with 74.3 DDDs/1000 inhabitants/day sold in 2016, followed by Finland (73.9), Sweden (54.4), Norway (43.8), and Denmark (31.8). Diclofenac use declined after 2008 in all countries but remained the most widely prescribed NSAID in Norway, with 63 prescription users/1000 inhabitants in 2016. Diclofenac sales also remained high in Iceland (12.7 DDD/1000 inhabitants/day), Norway (8.1), and Sweden (7.8). Since its introduction in 2003, the use of etoricoxib, a newer selective COX‐2 inhibitor, increased in all countries except Denmark, with highest sales in Finland (6.7 DDD/1000 inhabitants/day in 2016). Conclusion: Sales and prescription patterns of NSAIDs in the Nordic countries has changed along with the accumulating evidence for the cardiovascular risks of specific NSAIDs. However, given existing evidence on the cardiovascular risks associated with the use of diclofenac and etoricoxib, the persistent high use of diclofenac in Iceland, Norway, and Sweden, the persistent over‐the‐counter availability of diclofenac in Norway and Sweden, and the increasing use of etoricoxib in most of the Nordic countries pose a cardiovascular health concern.